2020
DOI: 10.1063/5.0012642
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed two-photon coherent control of channelrhodopsin-2 photocurrent in live brain cells

Abstract: Channelrhodopsin-2 (ChR2) is an ion channel activated by the absorption of light. A recent experiment demonstrated that the current emanating from neurons in live brain cells expressing ChR2 can be controlled using two-photon phase control. Here, we propose an experimentally testable coherent control mechanism for this phenomenon. Significantly, we describe how femtosecond, quantum coherent processes arising from weak-field ultrafast excitation are responsible for the reported control of the millisecond classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…This asymmetric V-shaped distribution in Figure 4C has been reported in previous scanning results of rhodopsin, 44 and Bucksbaum et al attributed this phenomenon to the combined effect of multiphoton excitation 45 and pump−dump effect. 46,47 For their experiment with rhodopsin, the dynamics by multiphoton excitation is faster than that by single-photon excitation.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This asymmetric V-shaped distribution in Figure 4C has been reported in previous scanning results of rhodopsin, 44 and Bucksbaum et al attributed this phenomenon to the combined effect of multiphoton excitation 45 and pump−dump effect. 46,47 For their experiment with rhodopsin, the dynamics by multiphoton excitation is faster than that by single-photon excitation.…”
supporting
confidence: 84%
“…This asymmetric V-shaped distribution in Figure C has been reported in previous scanning results of rhodopsin, and Bucksbaum et al. attributed this phenomenon to the combined effect of multiphoton excitation and pump–dump effect. , For their experiment with rhodopsin, the dynamics by multiphoton excitation is faster than that by single-photon excitation. By increasing the pulse chirps, the instantaneous light intensity becomes lower, resulting in the multiphoton effect suppressed and single-photon excitation dominating, observing the slower dynamics as shown in the V-shaped distribution.…”
supporting
confidence: 77%
“…7,8,18 In the fast C1 / O1 transition, the peak current is proportional to the amount of O1. 19 Bamann et al 20 activated ChR2 by using a short laser pulse (480 nm, 10 ns) and the results revealed four relaxation processes with different time constants during the photocycle of ChR2. This suggested four different intermediates (designated as P1, P2, P3, and P4) were formed in the photocycle induced by photoisomerization of retinal.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent control of atomic and molecular processes (for a review until 2012, see [1]), i.e., the use of quantum interference to effect molecular outcomes, has proven enormously successful for certain classes of processes. These include assorted processes, such as light-induced control of unimolecular processes such as photodissociation [2], photoionization [3], control of currents in live brain cells [4], control of population transfer between system eigenstates [5], control of internal conversion [6], etc. By preparing multiple interfering pathways as initial states, primarily by laser excitation, quantuminterference-based control over various processes, has been demonstrated both computationally (e.g., [1,[7][8][9]) and experimentally (e.g., [10][11][12]).…”
mentioning
confidence: 99%